MOTIVASI KERJA DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SMP MAARIF NU DI KABUPATEN BANYUMAS - Muakhir Muhamad Agus; Adityo Nugroho; Agung Prasetyo (Economics, Social, and Humanities Journal (Esochum), 2023)
This study aims to analyze the effect of compensation, ability, motivation, and the principal's performance on teacher performance at SMP Ma’arif NU in Banyumas Regency. Analyzing the principal’s compensation, ability, motivation, and leadership, which have the most dominant positive effect on teacher performance at SMP Ma’arif NU in Banyumas Regency. This study uses quantitative research methods. Sampling In the study, we used a probability sampling technique, proportional stratified random sampling. The research data was obtained by distributing questionnaires about compensation, ability, motivation, and the principal’s leadership to 68 respondents. Data analysis was carried out with the statistical tool used as multiple regression using SPSS 20. Statistical software. The result of this study indicates in the F Test (simultaneous) that compensation, ability, motivation, principal’s performance is significantly 0.000 < 0.05 and Fcount 61.169 > F Table 2.52. That the dependent variable is simultaneously able to explain changes in the Independent variable. Compensacion variable standardized coefficient value (-0.08), tcount (-1.114) dan sig 0.270 > 0.05 it can be concluded that the compensation variable has a negative effect on teacher performance the ability variable shows the significance value of standardized coefficients 0.687, and tcount (8.796) and sig 0.000 < 0.05 it is concluded that the ability has a positive influence on teacher performance. Motivation value standardized coefficients 0.397 t count 4.184 and sig 1.00 < 0.05 it can be concluded that the motivation variable has a positive influence on teacher performance. The variable of school principal's leadership values standardized coefficients(-0.098), tcount (-1.168) and sig 0.247 > 0.005 it is concluded that the principal’s leadership variable has a negative influence on teacher performance. The results showed that in the multiple regression analysis with the largest value of standardized coefficients 0.687 was the ability variabel. It is concluded that the most dominant variable that has a positive effect on teacher performance is the ability variable.